Preoperative Patient-Reported Outcomes May Help Predict Discharge Disposition after Total Hip Arthroplasty - Karia, Raj; Novikov, David; Gotlin, Matthew; Feng, James E.; Anoushiravani, Afshin A.; Slover, James D. (The Journal of Hip Surgery, 2019)
Patient-reported outcome (PRO) instruments are measures that allow for a standardized assessment of a patient's functional status, symptoms, and quality of life (QoL) through self-reported questionnaires. The purpose of this study was to assess the relationship between PRO scores, which measure patients' preoperative pain and functional status, and discharge disposition in the total hip arthroplasty (THA) population. The authors conducted a retrospective review of patients with a primary diagnosis of osteoarthritis who underwent THA at a single, urban, tertiary care center between September 2013 and August 2016. Patient demographics and preoperative PRO scores (Hip Disability and Osteoarthritis Outcome Score [HOOS] and EuroQol 5-Dimension [EQ-5D] questionnaire) were collected, and discharge disposition was categorized into the following two cohorts: THA recipients discharged to home and those discharged to a postacute care facility. When comparing PRO scores between the two groups, patients discharged home were found to have significantly higher average preoperative global EQ-5D, EQ-5D-QoL, HOOS activities of daily living (ADL), HOOS pain, HOOS sports, and HOOS symptoms scores. Patients discharged home trended toward higher HOOS QoL scores (28.1 vs. 22.6%), but this did not achieve significance (p < 0.08). The authors found a significant relationship between patients' baseline PRO scores and discharge disposition following THA. Patients discharged home had significantly higher preoperative PRO scores as measured by EQ-5D and HOOS. This demonstrates that patients with lower baseline PRO scores, indicating lower baseline function, may require additional care following surgery. These scores provide surgeons with an objective parameter that can assist in the planning and coordination of postoperative care. This study was a level III retrospective cohort.
Keywords: total hip arthroplasty; patient-reported outcome; discharge disposition; value-based care